A caracterização textual-discursiva do artigo de divulgação científica - Silva, Rodrigo Leite da (2016)
This thesis comprises the popular science articles require treatment by Textual Linguistics, Discourse, complimented by Critical Discourse Analysis. Its theme the popular science articles published in the field of history, which treat of the Second Empire Imperial in Brazil and present the reconstruction of the main characters of this period are: From Pedro II and Princess Isabel. This thesis is justified, as popular science articles are organized by a narrative of scientific discovery in modified news event. The news event is guided from the selection of topics through the following categories: Offbeat and Current. Two popular science articles were analyzed that being a magazine published in Adventures in History and the other in the history of the magazine National Library. The overall objective is to contribute to the studies of popular science discourse within the text and speech and specific: 1) To examine the textual construction, through textual sequences that are embedded in popular science article; 2) Analyze the processing of opinionated promoter of ratings in relation to the scientific findings produced by historical research. The results show that: the popular science article is a genre opinionated and his producer, the science writer, is one that produces opinions about the findings derived from the historical science, so that collaborate for the democratization of scientific knowledge. Opinions are built in accordance to company-Journal of interests. Therefore, the opinions produced by science communicators in popular science articles are arranged from facts and arguments of the promoter and are guided by the semantic categories of journalistic news (unusual and current)